Preoperative short-course radiotherapy and long-course radiochemotherapy for locally advanced rectal cancer: Meta-analysis with trial sequential analysis of long-term survival data. - Xin Wang; Bobo Zheng; Xinlan Lu; Ruhai Bai; Linlin Feng; Quan Wang; Yan Zhao; Shuixiang He (PLoS ONE)
Background and purpose The role of preoperative short-course radiotherapy (SCRT) in rectal cancer treatment, when compared to long-course radiochemotherapy (LCRT), is still controversial. Thus the meta-analysis with trial sequential analysis (TSA) was performed to evaluate the long-term survival of SCRT and LCRT as therapeutic regimens for locally advanced rectal cancer. Material and methods PubMed, Embase, and the Cochrane Central Register of Controlled Trials were searched up to August 2017 for eligible studies. Hazard ratios (HRs) or odds ratios (ORs) of overall survival (OS), disease free survival (DFS) and local recurrence (LR) with the corresponding 95% confidence intervals (CIs) were calculated and TSA was applied. Results 11 studies with 1984 patients were included. There was no significant difference in OS (HR = 0.92, 95% CI: 0.75-1.13, p = 0.44), DFS (HR = 0.94, 95% CI: 0.79-1.12, p = 0.50) and LR (OR = 0.73, 95% CI: 0.49-1.08, p = 0.11) between SCRT and LCRT groups. TSA suggested firm evidence for lacking on average a -10% relative risk reduction (RRR) in 4-year OS but no statistical significance in 4-year DFS. Conclusions Preoperative SCRT is as effective as LCRT for locally advanced colorectal cancer in long-term survival. SCRT could be preferential while facing long waiting lists or lacking medical resource.